Formula to Find y Intercept
Before learning the formula to find the yintercept, first, we will recall what is meant by a yintercept. The yintercept of a function is a point where its graph would meet the yaxis. The xcoordinate of any point on the yaxis is 0 and we use this fact to derive the formula to find the yintercept. Let us learn the formula to find the yintercept along with a few solved examples.
What Is the Formula to Find y Intercept?
In the earlier section, we have seen that the yintercept is a point on the yaxis and hence its xcoordinate is zero. Thus, to find the yintercept of a function y = f(x),
 we just substitute x = 0 in it.
 solve for y.
Thus, the formula of finding the yintercept is:
The yintercept of a function is of the form (0, y). Let us see the applications of the formula to find the yintercept in the following section.
Solved Examples Using Formula to Find y Intercept

Example 1: Find the yintercept of the following functions using the formula to find the yintercept: a) y = x^{2}  3x + 2 b) y = (x^{2}  1) / x
Solution:
To find: The yintercepts of the given functions.
To find the yintercept of a function, we just substitute x = 0 in it and solve for y.
a) Substitute x = 0 in y = x^{2}  3x + 2, we get
y = 0^{2}  3(0) + 2 = 2
So its yintercept = (0, y) = (0, 2)
b) Substitute x = 0 in y = (x^{2}  1) / x, we get
y = (0^{2}  1) / 0 = 1/0 = Not defined
So the given function doesn't have a yintercept.
Answer: a) (0, 2); b) Does Not Exist

Example 2: If the yintercept of a function y = a (x  1) (x  2) (x  3) is (0, 12), then find the value of "a".
Solution:
To find: The value of "a".
The equation of the given function is:
y = a (x  1) (x  2) (x  3)
Using the formula to find the yintercept, it can be obtained by substituting x = 0 in it.
y = a (0  1) (0  2) (0  3) = 6a
So the yintercept is (0, 6a)
But the problem says that the yintercept of the given function is (0, 12). Thus,
6a = 12
Dividing both sides by 6,
a = 2
Answer: a = 2